2020
DOI: 10.1016/j.ajem.2020.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19) and ischemic colitis: An under-recognized complication

Abstract: COVID-19 has spread worldwide, with more than 2.5 million cases and over 80,000 deaths reported by the end of April 2020. In addition to pulmonary symptoms, gastrointestinal symptoms have been increasingly recognized as part of the disease spectrum. COVID-19-associated coagulopathy has recently emerged as a major component of the disease, leading to high morbidity and mortality. Ischemic colitis has been reported to be associated with a hypercoagulable state. To our knowledge, there have not been any case repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 21 publications
0
60
0
1
Order By: Relevance
“…Some studies used abdominal diagnostic imaging in patients with SARS-CoV-2 infection to assess their intestinal condition and provide evidence for GI involvement. The most frequently reported observations are intestinal ischemia, including vessel thrombosis/embolism in the small bowel and/or colon and ischemic colitis [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Bhayana et al examined 42 abdominal CT scans of 412 hospitalized patients with COVID-19 [ 48 ].…”
Section: Clinical Gi Featuresmentioning
confidence: 99%
“…Some studies used abdominal diagnostic imaging in patients with SARS-CoV-2 infection to assess their intestinal condition and provide evidence for GI involvement. The most frequently reported observations are intestinal ischemia, including vessel thrombosis/embolism in the small bowel and/or colon and ischemic colitis [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Bhayana et al examined 42 abdominal CT scans of 412 hospitalized patients with COVID-19 [ 48 ].…”
Section: Clinical Gi Featuresmentioning
confidence: 99%
“…Deep vein thrombosis and pulmonary thromboembolism are one of the most severe consequences of this vascular disease. On the other hand, hemorrhagic colitis, an under-recognized COVID-19 complication, may occur due to microangiopathy of the intestinal vasculature [ 10 ].
Fig.
…”
mentioning
confidence: 99%
“…It was suggested that the hypercoagulability observed in COVID19 was related to the high inflammatory state associated with a “cytokine storm” rather than a progression of disseminated intravascular coagulation (DIC) [ 3 ]. To our knowledge, few cases of SARS-CoV-2- induced ischemic colitis have been reported [ 1 ] and none of them with a massive short bowel resection with short bowel disease as final result.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic colitis has been reported to be associated with a hypercoagulable state, However few cases have been reported of COVID-19 associated with ischemic colitis [ 1 ].…”
Section: Introductionmentioning
confidence: 99%